DISTRIBUTION OF LENGTH, LENGTH-WEIGHT RELATIONSHIP, AND CATCHABLE SIZE OF ALBACORA IN BENOA PORT - Roma Yuli Hutapea; Made Mahendra Jaya; Elsari Tanjung Putri (BAWAL Widya Riset Perikanan Tangkap, 2025)
Albacore (Thunnus alalunga) is one of the most economically important tuna species in tropical waters, including Indonesia. High levels of tuna exploitation can be minimized through fisheries management that requires stock and biological data.  The purpose of this study was to analyze the size distribution, percentage of fish suitable for capture, and the relationship between length and weight of Albakora (Thunnus alalunga) landed at Benoa Port. The study was conducted from January to April 2024 by taking 200 samples of Albakora (Thunnus alalunga) landed at Benoa Port. The analysis methods used were length distribution, length and weight relationships, and catchable size of Albacore (Thunnus alalunga). The analysis results showed that the frequency distribution of Albacore (Thunnus alalunga) length was highest in the range of 100 cm – 106 cm, with 66 fish. A total of 85% of Albacore (Thunnus alalunga) were in the catchable category, while 15% were in the non-catchable category. Albacore growth is negatively allometric (b<3), meaning that fish length grows faster than weight. The condition of Albacore fisheries in the Indian Ocean is classified as overfishing, thus requiring proper management...